Acute on chronic heart failure—Which variations on B‐type natriuretic peptide levels?. Issue 3 (18th June 2021) - Bettencourt, Paulo; Chora, Inês; Silva, Filipa; Lourenço, Patrícia; Peacock, W. Frank
Abstract: Objective: Natriuretic peptides are useful diagnostic and prognostic markers in patients presenting to the emergency department (ED) with acute shortness of breath. However, B‐type natriuretic peptide (BNP) level represents a single snapshot in time, while changes relative to a patient's baseline may be useful in risk stratification. We aimed to define the variation of BNP levels between chronic stable and acute decompensated heart failure (ADHF) that is associated with significant clinical outcomes. Methods: We performed a retrospective cohort chart review study of chronic heart failure (HF) patients followed in an outpatient clinic from 2010 to 2013. Inclusion criteria were available hospital and clinic BNP levels and at least 1 year of follow‐up care. ADHF was defined as a hospital admission for acute HF. Dry BNP was defined as its concentration after >3 months of optimal treatment and no variations in New York Heart Association class. Dry BNP was compared to the BNP at a subsequent ED visit that was associated with hospitalization because of ADHF. Results: Overall, 253 patients were included. Their median (interquartile range [IQR]) dry BNP was 191(83–450) pg/mL. There were 67 ADHF admissions, occurring 15 ± 15 months after patient's dry BNP was established. At subsequent ED admission, the median (IQR) BNP was 1505 (72–2620) pg/mL. Patients requiring inpatient admission had a BNP ∼250% higher than their stable BNP (404 vs 164 pg/mL, p < 0.001). Conclusions: In this group of chronic stable HF patients, a doubling of BNP was observed in patients who required hospitalization for acute decompensated HF. BNP doubling may represent a useful parameter to reflect clinically relevant acute decompensated HF.